Resilience in the face of innovation: Household trials with BubbleBoard - Lindley, Siân; Banks, Richard; Harper, Richard; Jain, Anab; Regan, Tim; Sellen, Abigail; Taylor, Alex (International Journal of Human-Computer Studies, 2009)
We present the results of a field trial in which a visual answer machine, the BubbleBoard, was deployed in five households. The aims of the trial were to create an improved answer machine, but also, and more interestingly, to encourage family members to appropriate it through the inclusion of open and playful design elements. Through making aspects of audio messages visible, BubbleBoard offered a number of improvements over existing answer machines. However, the new affordances associated with this were not appropriated by family members in the ways we had expected. We discuss possible reasons for this, and conclude that attempting to encourage appropriation through ‘openness’ in design may not be sufficient in the face of well-established social practices.